2018
DOI: 10.1247/csf.17023
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar-associated Protein FAP85 Is a Microtubule Inner Protein That Stabilizes Microtubules

Abstract: ABSTRACT. Genomics and proteomics studies in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…This means that the degree of inherent tension inside the doublet can be changed by external cues. There are a few MIP candidates with calcium binding domain, such as Rib72a (11) and FAP85 (21). Thus, MIPs can exploit the tubulin conformational change as a tool to modify the rigidity of the doublet and, thus, ciliary bending (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the degree of inherent tension inside the doublet can be changed by external cues. There are a few MIP candidates with calcium binding domain, such as Rib72a (11) and FAP85 (21). Thus, MIPs can exploit the tubulin conformational change as a tool to modify the rigidity of the doublet and, thus, ciliary bending (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is nearly twice of the sum of RIB72A and RIB72B (133 kDa), suggesting that either multiple copies of each RIB72 proteins are involved, or that additional, unidentified proteins contribute to these MIP-supra-complexes. A recent biochemical and immuno-gold labeling study suggested that the EF-hand containing protein FAP85 is an A-tubule MIP and may be associated with the MIP1 structure in Chlamydomonas flagella (Kirima and Oiwa, 2017).…”
Section: Rib72a and Rib72b Are Conserved Mips Required For The Assembmentioning
confidence: 99%
“…Whereas singlet cytoplasmic microtubules are usually characterized by dynamic instability, doublet and triplet microtubules form a highly stable scaffold, which serves as a platform for a plethora of associated proteins. A common structural feature shared by doublets, triplets, and other highly stable microtubules, such as the subpellicular and ventral disc microtubules of the pathogens Plasmodium and Giardia, respectively, is the presence of a unique class of microtubule associated proteins, called Microtubule Inner Proteins (MIPs) that are regularly distributed along the luminal surface of the microtubules (Nicastro et al, 2006;Nicastro et al, 2011;Maheshwari et al, 2015;Ichikawa et al, 2017;Kirima and Oiwa, 2017). The 3D structures and periodicities of MIPs have been best described in doublet microtubules (DMTs) of motile cilia where they assemble into a complex arrangement of at least 6 conserved MIP structures (Nicastro et al, 2006;Nicastro et al, 2011;Ichikawa et al, 2017) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1a) 7,21 . To date, two MIPs in the A-tubule have been identified by recent studies 22,23 . MIPs have also been observed in the axonemes of higher organisms 7,21,2426 , implying that these inner structures are essential for the integrity of DMTs in motile cilia and flagella.…”
Section: Introductionmentioning
confidence: 99%